Trait Kecemasan dan Gejala Gangguan Makan: Infleksibilitas Psikologis sebagai Mediator - Aleeza, Asaelia; Bintari, Dini Rahma (INSAN Jurnal Psikologi dan Kesehatan Mental, 2023)
The prevalence of eating disorder (ED) symptoms is increasing in emerging adults and have negative psychosocial impacts on the individuals. Anxiety has been found to precede the development of ED symptoms. This cross-sectional study aims to investigate the role of psychological inflexibility in the relationship between anxiety and ED symptoms in a sample of 141 female Indonesian emerging adults. Participants completed the adapted version of Trait anxiety subscale of the State-Trait Anxiety Inventory, the Acceptance and Action Questionnaire-II and Eating Attitudes Test-13 to assess trait anxiety, psychological inflexibility, and ED symptoms respectively. Results showed the indirect effect of trait anxiety and ED symptoms with psychological inflexibility as mediator was significant [b=0.144, 95%CI:(0.02-0.29)]. This suggests that psychological inflexibility can mediate the relationship between anxiety symptoms and ED symptoms. This finding may help creating prevention initiatives targeting psychological inflexibility for individuals vulnerable with anxiety to prevent the development of ED symptoms.